The Influence of Service Quality and Timeliness of Delivery on Customer Satisfaction at the Sicepat Express Delivery Service in Johar Baru, Central Jakarta - Pradini , Jahra (Logistica : Journal of Logistic and Transportation, 2023)
Online trading certainly requires goods delivery services. Inappropriate service quality can affect the business where customers can provide an assessment of the service, and timeliness can also affect customer satisfaction if it is not in accordance with the estimates provided by the delivery service. This study aims to analyze the effect of service quality and on time delivery on customer satisfaction at the SiCepat Ekspres delivery service in Johar Baru, Central Jakarta. This research method uses a quantitative method by using a questionnaire via google form. The population of this study was 12,633 of the Johar Baru SiCepat Ekspres customers in January-May 2023 by calculating the number of respondents using the slovin formula with a result of 100 respondents. With the results of service quality research (X1) has an influence on customer satisfaction of 56.5%. Timeliness of delivery (X2) has an influence on customer satisfaction of 72.3%. Service quality (X1) and timely delivery (X2) simultaneously influence customer satisfaction variable (Y) with a value of 73.5%, the remaining 26.5% is explained by other factors not included in this study.